Translation and validation of the Life Satisfaction Index for Adolescents scale with neuromuscular disorders: LSI-A Brazil - Simon, Valdecir Antonio; Zanoteli, Edmar; Simon, Margarete Andreozzi Vaz Pereira; Resende, Maria Bernadete Dutra de; Reed, Umbertina Conti (Arquivos de Neuro-Psiquiatria, 2017)
To validate the Life Satisfaction Index for Adolescents (LSI-A) scale, parent version and patient version, for Duchenne muscular dystrophy (DMD), spinal muscular atrophy (SMA) and limb-girdle muscular dystrophy (LGMD).The parent version of the instrument was divided into Groups A, B, C and D; and the patient version, divided into B, C and D. For the statistical calculation, the following tests were used: Cronbach’s α, ICC, Pearson and the ROC Curve.The parent and patient versions of the instrument are presented, with the following results in the overall score, respectively: Cronbach’s α, 0.87 and 0.89; reliability, r 0.98 and 0.97; reproducibility, ICC 0.69 and 0.80; sensitivity, 0.78 and 0.72; specificity, 0.5 and 0.69; and accuracy, 64% and 70.4%.According to the validity and reproducibility values, the LSI-A Brazil parent and patient versions, are clinically useful to assess quality of life in DMD, SMA or LGMD and may also be useful for other neuromuscular disorders.
Keywords: validation studies; quality of life; neuromuscular disorders